Therapeutic Approach to Post-Traumatic Headache in Brazil: A Literature Review - Santos, Isabela Cacau Sousa; Lima, Raynrich Kevin Assis; Lima, Rayndrick Kelryn Assis; Santos, Gabriela Cacau Sousa; Nogueira, André Marinho Paiva (Headache Medicine, 2023)
Full abstract in PDF.